HYPOFRACTIONATED RADIOTHERAPY WITH CONCURRENT CHEMOTHERAPY WITH WEEKLY CISPLATIN IN LOCALLY ADVANCED RELATIVELY RADIORESISTENT SUBSITES OF HEAD AND NECK CANCERS - Baidya, K.; Devi, Y. S.; Devi, A. S.; Singh, Y. I.; Das, D.; Mahawar, R.; Devi, N. N. (International Journal of Medicine and Medical Research, 2023)
Background. Locoregionally advanced head and neck cancers are more aggressive and locoregional failure rate after conventional radiotherapy is high. Objective. The aim of the study is to assess the tumor response and toxicities of hypofractionated radiation therapy with concurrent chemotherapy in treatment of four relatively radioresistent tumor sites of head and neck. Methods. A prospective randomised control trial was conducted in 27 head and neck cancer patients. All patients were treated with hypofractionated radiotherapy at 250cGy/fraction once daily to a maximum of 62.5Gy in 25 fractions with concurrent cisplatin 30 mg/m2. Data were evaluated with SPSS version 21.0 for Windows with p-value <0.05. Results. Complete and partial responses were achieved in 15 (57.7%) and 8 (30.8%) patients respectively with an overall response rate of 88.5% and three patients having stable disease. Grade 3 and 4 acute mucositis was experienced by 17 patients (65.4%) and seven patients (27%), respectively. Grade 3 dysphagia was found in 21 patients (80.7%) and grade 3 and 4 skin reactions – in 11 and 2 patients, respectively. Most patients had manageable acute toxicities. Most of the late complications were of grade 2 and 3. The median time to locoregional recurrence was 12 months and one year progression-free survival attained by 61.5% patients. Conclusion. Treatment with hypofractionated radiotherapy with concurrent cisplatin appears feasible and safe and is associated with a good response rate. Although grade 3 and 4 toxicities were comparatively high but it was manageable. Late toxicities were within tolerable levels.